Effectiveness of Sports-Based Interventions for Mental Health in At-Risk Youth: A Systematic Review - Rowińska, Katarzyna; Siembab, Karolina; Bednarczyk, Daria; Białeta , Julia; Napieralska, Agnieszka; Černohorská, Alicja; Garbarczyk, Wiktor; Jurkiewicz, Michalina; Kapla, Albert; Pysiewicz, Wiktoria (Quality in Sport, 2025)
Adolescents’ mental health is a growing public health concern, particularly for at-risk youth exposed to adverse circumstances such as poverty, trauma, discrimination, or social exclusion. These individuals face higher risk of developing mental health issues, including anxiety, depression, and post-traumatic stress disorder (PTSD), which can significantly impact their education, social interactions, and long-term well-being. Addressing these challenges requires holistic, non-stigmatizing approaches, which will be tailored to the unique needs of at risk youth. Sports-based interventions have emerged as a promising strategy to promote mental health by leveraging the psychological and social benefits of physical activity. This systematic review analyses the effectiveness of sports-based interventions in improving mental health outcomes in at-risk youth, focusing on areas such as anxiety, depression, PTSD, self-esteem, social skills, and emotional regulation.